Efeito da prática do muay thai sobre a aptidão física em mulheres ativas - Sousa, Victor Silva de (Brasil, 2025)
Muay Thai is a combat sport originally from Thailand. It is characterized by being a martial art that uses fist strikes, elbows, knees, shins and feet. It is a dynamic and challenging sport that combines technique, strength, agility and strategy. In addition to being an effective form of self-defense, it provides practitioners with an experience of personal, cultural and spiritual growth. The study aimed to investigate evidence on the effect of practicing Muay Thai in relation to health-related physical fitness in adult women. Through a narrative review of studies published between 2009 and 2024, the article examines the physical and psychosocial benefits of regularly practicing Muay Thai. The studies analyzed indicate that practicing Muay Thai can lead to significant improvements in body composition, agility, upper limb speed, flexibility and other physical fitness variables. However, these improvements are not determined solely by practice time, suggesting that other factors such as training frequency and intensity, diet and adequate rest may play an important role. The article concludes that practicing Muay Thai can be an effective strategy for promoting health and physical fitness in women, although more research is needed to explore these effects in more depth.